RENEWABLE ENERGY INVESTMENT AND ITS ECONOMIC SPILLOVER EFFECTS IN UZBEKISTAN - Murodjon Sagdiddinov (Modern American Journals, 2025)
This paper focuses on the investment aspects of renewable energies within Uzbekistan and their additional economic consequences from the perspective of an emerging market economy. It also analyzes Uzbekistan’s transformation from an energy system predominantly reliant on fossil fuels to one harnessing cleaner energy alternatives while looking at the role of institutional transformations, foreign collaborations, and infrastructure initiatives. Through policy and project analysis along with empirical evidence, this paper evaluates the effects of renewables on workforce opportunities, industrial growth, technological advancement, and public finance. This study also describes some proprietary and regulatory gaps, like the grid limitation, perception of risk, especially regarding investment, and availability of talent. The study's results reveal that investments in renewable energy resources are impacting the diversification of energy resources and accelerating the modernization of the macroeconomic system in Uzbekistan. This experience can serve as a reference for other developing countries trying to use clean energy solutions for environmental challenges and as a strategic instrument for sustainable growth.
Keywords: Uzbekistan, renewable energy investment, economic spillover effects, emerging markets, solar power, wind energy, energy policy, green transition, foreign direct investment, energy sector reform